Epistemic dimensions of personhood - Evnine, Simon (Oxford : Oxford University Press, 2008)
Simon Evnine argues that all persons must share certain epistemic features. They must possess particular logical concepts and their beliefs must conform to certain principles of rationality. However, they cannot be completely objective about their own beliefs. These features deepen our understanding of what it is to be a person.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Persons; Philosophical anthropology